Business process management within chemical and pharmaceutical industries : Markets, BPM methodology and process examples - Grune, Guido (Springer Berlin Heidelberg, 2014)
As business processes are crucial success factors for companies, software-based Business Process Management (BPM) is becoming more and more important. In this area SAP, the market leader for enterprise application software, has already gathered substantial experience. For the characterization, modeling and especially the optimization of business processes, SAP's consultants use their own BPM approach. In addition to their considerable methodological know-how, the consultants' profound knowledge of the industries facilitates the focus on core and business-critical processes. This book examines the current market situation, as well as the specific challenges and trends for the chemical and pharmaceutical industries. It also explains business process management basics and the specific SAP Consulting methodology, before illustrating the use of such methods and procedures with sample industry-specific core business processes. With the help of these examples from the chemical and pharmaceutical industries, SAP Consulting provides methodological guidelines on how Business Process Management can be used in practice to optimize business processes and make adjustments in response to constantly changing economic and environmental factors.